Acesso e adesão à terapia antirretroviral para o HIV/AIDS na Paraíba : uma reflexão desde a antropologia da saúde. - Medeiros, Marco Túlio Alves de (2024)
This monography is the result of four years of research on the topic of HIV/AIDS in Paraíba, initiated as a Scientific Initiation project titled "Faces and phases of HIV/AIDS in Paraíba" at the Federal University of Paraíba. It aims to qualitatively analyze, from anthropological and sociological perspectives, the management of antiretroviral treatment in Paraíba. The research involved meetings with Non-Governmental Organizations that are part of the "HIV/AIDS ONG Forum," participant observation at meetings of the Department of HIV, AIDS, Tuberculosis, Viral Hepatitis, and Sexually Transmitted Infections in Paraíba, two interviews with People Living with HIV/AIDS, and virtual ethnography on Facebook with two groups discussing HIV/AIDS, targeting both those undergoing treatment and those focused on prevention. The thesis specifically addresses aspects such as access to medication within the population, the challenges and facilitators of maintaining adherence to treatment once individuals enter antiretroviral therapy—whether these are due to adverse drug effects, interactions with other medications, personal choices, or specific issues analyzed in the field, particularly those related to subjective matters like stigma. In conclusion, while structural aspects are somewhat lacking, Paraíba shows strong behavioral monitoring, along with noted advancements in the latter